A New Approach to the Theory of Hierarchic Wave-oscillation Dynamic Systems - Kulish, V. V.; Gubanov, I. V.; Dien, Le Huu; Viet, Nguyen Ai; Lysenko, O. V. (Communications in Physics, 2009)
A set of new ideas and concepts (which the authors treat as a new version of the theory of hierarchic dynamic systems) are set forth in the article. In turn, the set of hierarchic principles is put in the methodological basis of this theory. It is shows, a peculiar version of the theory of hierarchic waves and oscillations can be developed on the basis of proposed general theory.